Intra-Articular Giant Synovial Osteochondroma: Case Reports of the Ankle and Knee Joint - Paolo Fornaciari; Pascal A. Schai; Richard Niehaus; Ulrich G. Exner (Case Reports in Orthopedics)
Two cases of giant intra-articular osteochondromas (knee and ankle joint) are reported; pathologically they are rare representations of synovial chondromatosis. A 17-year-old man presented with a tumorous mass which had been localized in his left ankle for many years, increasing in volume during the last months. The lesion was removed by posteromedial ankle arthrotomy. The second case was observed in a 39-year-old woman with a slow-growing mass in her right knee joint. The lesion was removed from the Hoffa fat pad by open anteromedial arthrotomy.